การจัดการการเรียนรู้เพื่อเพิ่มศักยภาพของทรัพยากรมนุษย์ต่อการยกระดับเศรษฐกิจและสังคมของภาคชนบทและชุมชนเมือง จังหวัดเชียงใหม่ - สุระ, กาญจนา (Community and Social Development Journal, 2011)
บทคัดย่อภาษาไทยไม่สมบูรณ์ Learning Management to Increase the Potential Capacity of Human Resources in Enhancing the Economic and Society of Chiang Mai Rural and Urban Areas The main objective of this study was to investigate managing of learning management in order to increase human resource potential capacity to enhance the economic and society in rural and urban areas of Chiang Mai. Participatory action research and SWOT analysis were conducted. The target group consisted of 58 local administrative organizations from 19 districts based on local socio-economic plans. 32 local administrative organizations are interested in developing economic plan. 26 local administrative organizations are interested in developing social plan and one of these 26 organizations is the local administrative organization of the district in Chiang Mai. The sample group selected by purposive sampling was composed of 58 representatives from local administrative organizations and 58 representatives from local communities who joined in developing the socio-economic plans in this project . Basic information was concerned with the potential of local community in socio-economic survey with the evaluation of the potential capacity of the sample groups; thinking, management, knowledge and skill as well as potential mental capacity. Descriptive analyses by percentage were used to analyze the data. Managing learning management to increase the potential capacity of human resources consisted of 1) learning management to analyze the potential capacity of human resources; 2) learning management to bring a body of knowledge concerning management to perform in local communities; 3) learning management for creative thinking; 4) learning management to pass on the body of local wisdom to youth; 5) learning management for cooperation between government and communities. The evaluation of the potential capacity of the representatives was that the representatives from both local administrative organizations and local communities who are interested in developing their economic plan have 53.12 percent increased in their creativity, knowledge and ability, patience and collaboration as well as management. Local administrative organizations join in social development have 53.84 percent increased in creative thinking, knowledge and skill, patience and collaboration as well as management. 9.37 percent of samples who are representatives from local administrative organizations and local communities and interested in developing economic plan have no capacity increased. 46.15 percent of representatives from local administrative organizations and local communities and interested in developing social plan have no capacity increased.